Forespore-Specific Transcription of the lonB Gene during Sporulation in Bacillus subtilis - Serrano, Monica (American Society for Microbiology, 2001)
The Bacillus subtilis genome encodes two members of the Lon family of prokaryotic ATP-dependent proteases. One, LonA, is produced in response to temperature, osmotic, and oxidative stress and has also been implicated in preventing ς(G) activity under nonsporulation conditions. The second is encoded by the lonB gene, which resides immediately upstream from lonA. Here we report that transcription of lonB occurs during sporulation under ς(F) control and thus is restricted to the prespore compartment of sporulating cells. First, expression of a lonB-lacZ transcriptional fusion was abolished in strains unable to produce ς(F) but remained unaffected upon disruption of the genes encoding the early and late mother cell regulators ς(E) and ς(K) or the late forespore regulator ς(G). Second, the fluorescence of strains harboring a lonB-gfp fusion was confined to the prespore compartment and depended on ς(F) production. Last, primer extension analysis of the lonB transcript revealed −10 and −35 sequences resembling the consensus sequence recognized by ς(F)-containing RNA polymerase. We further show that the lonB message accumulated as a single monocistronic transcript during sporulation, synthesis of which required ς(F) activity. Disruption of the lonB gene did not confer any discernible sporulation phenotype to otherwise wild-type cells, nor did expression of lonB from a multicopy plasmid. In contrast, expression of a fusion of the lonB promoter to the lonA gene severely reduced expression of the ς(G)-dependent sspE gene and the frequency of sporulation. In confirmation of earlier observations, we found elevated levels of ς(F)-dependent activity in a spoIIIE47 mutant, in which the lonB region of the chromosome is not translocated into the prespore. Expression of either lonB or the P(lonB)-lonA fusion from a plasmid in the spoIIIE47 mutant reduced ς(F) -dependent activity to wild-type levels. The results suggest that both LonA and LonB can prevent abnormally high ς(F) activity but that only LonA can negatively regulate ς(G).